Food retailer price convergence: the case of Tijuana, Mexico - Díaz , Eduardo R. (Frontera Norte, 2022)
The objective of this study is to compare prices across ten food categories sold by four large food retail chains in Tijuana, Baja California, Mexico. The data was collected through mystery shoppers across a seven-month period. The analysis consisted of descriptive statistics and analyses of variance (ANOVA). The results suggest that the retailers in the study apply similar prices across ten food categories. This is one of the few studies conducted in the region to address food price convergence in the retail sector. The conclusion is that price convergence takes places among large retail chains in Tijuana. The main limitation of the study is the geographic focus. The implications are that retailers find themselves struggling to differentiate based on price, and end up making unsupported claims around lowest-price value propositions. Future studies can argue whether price convergence limits consumer choices or keeps prices in check.